READING INTENSITY ON STUDENTS’ SPEAKING ABILITY - Fitrotul Mufaridah; Siti Lutfiyah (Universitas Muhammadiyah Jember, 2020)
Speaking as a language skill has been considered the most difficult one to master by the students especially in Songserm Wittaya School Songkla, Thailand. It was found that the majority of the students found it difficult to speak English fluently. As a productive skill, speaking is complex because learners need to acquire the accuracy and fluency in speaking. However, one EFL class showed a bit difference in the ability of speaking English because of their reading intensity. The design of the research was descriptive qualitative. The data were collected by a questionnaire for intensive reading and an interview on speaking to 30 students at 4/3 grade. The results of this research in general revealed that most of the students at grade 4/3 Thailand are good in speaking English due to their intensive reading that reached 50%. It was clearly seen from the analysis of some aspects of speaking (pronunciation, grammar, vocabulary, fluency and comprehension) in the interview section and questionnaire of reading intensity that 50% of the participants can speak English better through reading activity intensively. This finding implies that intensive reading has become a meaningful input for students’ speech production.